Analysis of the use of LCMS Moodle in the educational process of KSPU (Educational Dimension, 2020)
The article analyzes the experience of using a learning management system (LMS) Moodle in the educational process of Kryvyi Rih State Pedagogical University (KSPU) based on the results of the survey conducted in early March 2020 and the organizational and methodological support of the semester distance learning and summer credit and examination session of 2019–2020 academic year. It was found that lecturers under the age of 30 (in particular, with up to 3 years of experience) or over 60 years old need methodological assistance more often. First of all, the developed courses present digital educational resources in text format, video and audio are not used enough. LMS Moodle is mainly used during examinations and credits, tests, and students’ independent work, while it should be used more intensively during lectures, laboratory, and practical classes. The generalized results of the survey led to the need to improve the level of ICT competence of teachers and students, to popularize the potential of LMS Moodle among them. In order to solve these tasks a number of measures were taken: groups of informational-technical, organizational and methodological support were formed by the quantity of scientific and pedagogical staff who have significant experience in LMS Moodle use; long courses, periodical seminars, consultations where both general questions of educational process organization in LMS Moodle were held as well as questions due to the specialties, internal and external expert evaluation of e-learning courses quality were covered.